IGF-1 and IGFBP-3 in Inflammatory Cachexia - Ana Isabel Martín (International Journal of Molecular Sciences, 2021)
Inflammation induces a wide response of the neuroendocrine system, which leads to modifications in all the endocrine axes. The hypothalamic–growth hormone (GH)–insulin-like growth factor-1 (IGF-1) axis is deeply affected by inflammation, its response being characterized by GH resistance and a decrease in circulating levels of IGF-1. The endocrine and metabolic responses to inflammation allow the organism to survive. However, in chronic inflammatory conditions, the inhibition of the hypothalamic–GH–IGF-1 axis contributes to the catabolic process, with skeletal muscle atrophy and cachexia. Here, we review the changes in pituitary GH secretion, IGF-1, and IGF-1 binding protein-3 (IGFBP-3), as well as the mechanism that mediated those responses. The contribution of GH and IGF-1 to muscle wasting during inflammation has also been analyzed.